Penerapan model pembelajaran open ended untuk meningkatkan keterampilan berpikir kreatif pada materi pengukuran sudut peserta didik kelas iv sekolah dasar - Alya Rahmawati Aziza; Sri Marmoah; Anesa Surya (Universitas Sebelas Maret, 2019)
Abstract. This research aimed to explain the creative-thinking skills of fourth-grade students to solving the angle measurement material by applying the open ended learning model. This research is Classroom Action Research with two cycles. The research subjects were 27 fourth-grade students of SD Negeri Tunggulsari I No. 72 in the 2018/2019 academic year. The data were collected with interviews, observations, essay test, and documentation using data analysis of source triangulation and technique triangulation. They were analysed using statistic descriptive and interactive analysis. The initial conditions of creative thinking skills of fourth-grade students showed 0% classically. The first cycle began with the first learning classified as high based on the percentage in the creative category of 7% in classical, the second learning was 26% in classical, and the third learning was 44% in classical. The research continued with the second cycle with the first learning showed 59% in classical, the second learning was 74% in classical, and the third learning was 85% in classical. This research is a preliminary research to apply mathematical learning models based on open ended in improving creative thinking skills.Keywords: creative thinking skills, open ended learning model, angle measurement, elementary school